PATH-62. QUANTITATIVE ANALYSIS OF SEX-ASSOCIATED MGMT METHYLATION IN NEWLY DIAGNOSED GLIOBLASTOMA. (11th November 2019) - Barnett, Addison; Saeed Bamashmos, Anas; Li, Hong; Bosler, David; Lathia, Justin; Yeaney, Gabrielle; Ali, Assad; Sagar, Soumya; Mohammadi, Alireza; Stevens, Glen; Angelov, Lilyana; Peereboom, David; et al.
Abstract: INTRO/OBJECTIVE: Glioblastoma (GBM) and MGMT have been reported to have sexual dimorphism. In multiple studies, including our own population-based cohort analysis, females had higher rates of MGMT methylation and improved methylation-associated progression-free and overall survival outcomes compared to males. MGMT methylation is assessed as a mean of five cysteine-phosphate-guanine (CpG1-5) islands (CpG methylation is highly inversely correlated with MGMT RNA expression). The primary objective of this study was to investigate differences in mean and individual CpG methylation by sex. METHODS: 155 patients who underwent first surgical intervention for newly diagnosed GBM at a single tertiary care institution between 2016 and 2018 were reviewed. Of these, 135 patients had available CpG methylation data determined by a clinically validated test using bisulfate conversion followed by PCR and pyrosequencing. MGMT was defined as methylated if the mean of CpG1-5 ≥ 12. The mean of CpG1-5 and each CpG parameter were compared by sex using the Wilcoxon signed-rank test. RESULTS: Overall (mean age 62, 34% female, 42% MGMT methylated), the median (IQR) of mean degree of methylation was 4.0% (2–33) and median CpG1-5 ranged from 3.0 to 4.5%. More females (53.3%) were MGMT methylated than males (37.1%). Females had significantly higher rates of mean methylation compared to males (14.0 vs 3.0%, p=0.046). Females also had higher rates of methylation at each CpG island compared to males CpG1(7.0 vs 3.0%, p=0.15), CpG2(8.0 vs 4.0%, p=0.10), CpG3(9.0 vs 4.0%, p=0.23), CpG4(7.0 vs 3.0%, p=0.047), and CpG5(6.0 vs 4.0%, p=0.097). CONCLUSION: Females had higher rates of mean methylation and methylation of each CpG island compared to males, although only mean and CpG4 methylation values were statistically significant given the limited sample size. Further investigation with a larger cohort is ongoing to elucidate this dimorphism and establish whether sex-specific methylation cut-offs need to be implemented into clinical practice.